Prevalence and Factors Affecting Mental Health among Older Adults: A Cross-Sectional Study in Rural South Karnataka - Sivapria K; Kalesh P S (Healthline)
Introduction: Ageing is a lifelong process of growing up and growing old. It begins at conception and ends with death. It is important to take into account the various physical and mental health issues that older adults experience. Objective: To determine the prevalence and factors affecting mental health among older adults. Methods: A cross-sectional study was conducted between January to June 2022 in the rural field practice area of tertiary care hospital in South Karnataka. Complete Enumeration method was used, total of 780 participant were interviewed using a semi-structured proforma. Mental health was assessed using General Health Questionnaire-12 (GHQ-12) which is a a short, self-administered questionnaire. Descriptive statistics were calculated using the mean, standard deviation, and proportion. To assess the relationship between risk factors, the chi square test was employed. Results: Using the GHQ-12 scoring, 50.4% of the older adults had mild distress & 18.6% of the older adults had severe distress. The factors affecting mental health were increase in age (p value<0.001), females (p value<0.01), poor occupational status (p value<0.001), poor socioeconomic status (p value<0.05), locomotor disability (p value<0.001) & those who suffered physical/mental abuse (p value<0.001). Conclusion: The mental health of older adults is at stake. It was observed that stress was seen with increasing age, females, unemployment, lower socioeconomic status, broken family, hypertension, lack of social support, disability, and abuse.